The role of ultrafast torsional relaxation in the emission from polythiophene aggregates - Parkinson, P; Müller, C; Stingelin, N; Johnston, M; Herz, L (2010)
An understanding of aggregation effects in organic semiconductors is essential for their effective use in optoelectronic devices. Typically, the electronic dynamics in such systems are heavily dependant upon the aggregation state, and dynamics often occur on sub-nanosecond timescales. © 2010 IEEE.